Conceptualizing the parallax of movement control orders (MCOs) to the spatial dispersion of PM10 - Noraain Mohamed Saraf; Nursyahreen Aqilah Mohmad Rassid; Siti Aekbal Salleh; Nurul Amirah Isa; Ameerah Su’ad Abdul Shakor; Muhammad Alfatih Pahrol (Songklanakarin Journal of Science and Technology (SJST), 2022)
Due to the COVID-19 pandemic, many countries have implemented movement control orders (MCO). Globally, including in Malaysia, such bans have reduced pollution. Thus, this study used remote sensing to examine the particle dispersion and intensity of PM10. Unlike previous research, this technique used Landsat 8 Operational Land Imager (OLI) satellite images to estimate anthropogenic level changes within the study area. Eight models are used to estimate PM10 levels. The models work well because they were developed and tested in India, which has a similar climate to Malaysia. Two models returned results that matched the study area's CAQMs station. Between 10th March 2020 and 26th March 2020 the CAQMS showed an average PM10 concentration of 17-32 g/m3 . The pixel based PM10 estimation is 30-35% off in g/m3 . However, the percent reduction of PM10 before and during MCO was within 2% of Model 5 and 7. Incorporating geospatial technology into baseline studies to assess current air quality is clearly beneficial. Since the first MCO in March 2020, toxic pollution emissions have decreased significantly.